2021
DOI: 10.21680/2176-9036.2021v13n1id19637
|View full text |Cite
|
Sign up to set email alerts
|

Traços de personalidade e variáveis do comportamento planejado do indivíduo: um estudo de seus efeitos nas intenções empreendedoras

Abstract: Objetivo: Este estudo tem como objetivo investigar quais os efeitos dos traços de personalidade sobre as intenções empreendedoras dos alunos concluintes dos cursos de Ciências Contábeis de duas instituições de ensino superior privadas e uma pública, localizadas na região centro-oeste do Brasil. Metodologia: Estudo descritivo, realizado a partir de uma pesquisa de levantamento, com a amostra constituída por 173 alunos sendo 86 de uma universidade pública e 87 de duas universidades privadas. O instrumento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Thus, both students in the first and last semesters of the undergraduate programs present attitudes congruent with entrepreneurial intention. Similar evidence was observed with Brazilian (Santos et al, 2021), Vietnamese (Doanh & Bernat, 2019), Spanish (Miranda et al, 2017), and Greek (Tsordia & Papadimitriou, 2015) business students. This finding also suggests that attitude -amidst the elements of the TPB -is a strong determinant of entrepreneurial intention and behavior since students appreciate the entrepreneurship career (Küttim et al, 2014), and this career requires attitudes and autonomy from individuals.…”
Section: Figure 2 -Synthesis Of Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Thus, both students in the first and last semesters of the undergraduate programs present attitudes congruent with entrepreneurial intention. Similar evidence was observed with Brazilian (Santos et al, 2021), Vietnamese (Doanh & Bernat, 2019), Spanish (Miranda et al, 2017), and Greek (Tsordia & Papadimitriou, 2015) business students. This finding also suggests that attitude -amidst the elements of the TPB -is a strong determinant of entrepreneurial intention and behavior since students appreciate the entrepreneurship career (Küttim et al, 2014), and this career requires attitudes and autonomy from individuals.…”
Section: Figure 2 -Synthesis Of Resultssupporting
confidence: 83%
“…The scope of the study observing undergraduate programs of administration, accounting, and economics, and the absence of a consolidated list of students enrolled in these three areas of knowledge hindered the ability to determine the number of students forming the research population. However, this aspect does not affect the analysis and is in line with other studies on the subject (e.g., Miranda et al, 2017;Santos et al, 2021).…”
Section: Sample Instrument and Data Collectionsupporting
confidence: 87%
See 1 more Smart Citation
“…Through the integration of social competency and resilience into the entrepreneurial intention model, this study explores an unexplored attribute of entrepreneurs. Andrade et al (2021) [64] and Munir et al (2019) [37] refer to previous studies that found a link between the two via subjective norms. Based on these findings, these individuals are more likely to take the lead in making beneficial environmental changes, and they may even believe that there are positive subjective norms centred around starting a company with a focus on sustainability [65].…”
Section: H4mentioning
confidence: 99%
“…From the assumptions that beliefs are the cognitive bases of attitudes and behavioral intentions, Fishbein and Ajzen (1975) developed a model to predict human behavior (Behavioral Intentions Model), known as the Theory of Rational Action (TRA) Ajzen, 2020;Santos et al, 2021). After the completion of several studies on TRA, it evolved to TPB (Ajzen, 1991), also having behavioral, normative, and control beliefs as the focus of study.…”
Section: Behavioral Beliefsmentioning
confidence: 99%